The Volatility Of Return Of Malaysian Crude Palm Oil Futuresand Its Response On Trading Volume And Open Interes - Yeap, Xiu Wei (2024)
This study aims to examine the relationships between transformational leadership, team innovation climate, team reflexivity, psychological capital, environmental dynamism, and employee creativity within the context of the covid-19 pandemic-induced turbulent business environment. This study collected data from 406 individuals and 618 team-level individuals in chinese small and medium-sized manufacturing enterprises. The statistical analysis was conducted using spss 26 and mplus 8. A total of 16 hypotheses in this study investigated the influence of transformational leadership on employee creativity. Firstly, transformational leadership has a significant positive relationship with employee creativity. Secondly, the relationship between transformational leadership and employee creativity is mediated by three factors: team innovation climate, team reflexivity, and psychological capital. The results of this study also indicate that environmental dynamism moderates the relationship between transformational leadership and psychological capital, thereby strengthening the positive association between these variables.